Aplicativo BENE - A estatística a serviço da educação financeira - Lima, Francisca Tyara Mota (2023)
The perspective of this dissertation is to demonstrate how the knowledge of Statistics can go far beyond the classroom and collaborate with the community in general. From the creation of an application called BENE, high school students from the State School of Professional Education Adriano Nobre, located in the municipality of Itapajé/CE, became protagonists of their learning through the contextualization of the knowledge acquired in the classroom, about Statistics, using them not only to solve theoretical problems, but creating a tool that would contribute to the financial education of the entire school community. The developed application is intended for price consultation, in three local shops, of items that make up the basic food basket. In this, its users will be able to see the context of Statistics having contact with Measures of Central Trend, in the case of Mode and Arithmetic Mean, as well as the Measure of Dispersion called Standard Deviation. This work brings the theoretical foundation of Statistics, the description of the entire process of creation and presentation of the application, in addition to the opinion of school management, students and their guardians about the developed tool.